Optimizing Resource Sharing through Artificial Intelligence: A Management and IT Perspective - Roy, Devang; Kumar, Manoj K.; Ranjan, Vivek; Saikia, Nabajit (ADA University Library, 2024)
This poster explores the potential of Artificial Intelligence (AI) to optimize resource sharing in libraries and information centers. By addressing the challenges faced in traditional resource sharing methods, AI technologies can enhance efficiency, improve user experience, and facilities better management of information resources. The study discusses various AI applications that can be leveraged to improve resource sharing, focusing on their impact from both management and IT perspectives.
Keywords: Artificial intelligence in resource sharing; Library management systems; Information technology in libraries